Comparative Study Between Siomai Food Stalls and Siomai Food Carts on Marketing Mix in Brgy. Novaliches Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to compare the marketing mix of the Siomai Food Stalls andSiomai Food carts in terms of price, product, place, and promotions.The results of this study reveal that the majority of the respondents of Siomai Food Stalls andSiomai Food Carts are aged 18-23 years old; a bachelor`s degree is the highest educationalattainment. Then, their assessment of the marketing mix in terms of price, product, and placeare strongly agreed aside from promotion, and there is no significant difference between theassessment of the marketing Mix of Food Stall and Food Cart Siomai Businesses in terms ofplace, price, and promotion; there is a significant difference between and among theassessment on the marketing Mix of Food Stall and Food Cart Siomai Businesses in terms ofplace, price, product, and promotion and there are recommendations to proposed to enhancemore on their marketing mix.This study recommended that Siomai businesses need to market their businesses to the agesof 24-29 years old, and the Siomai Food Stalls and Siomai Food Carts must stay on what theyare practicing when it comes to being convenient and easy to reach by the customers andmust focus on their promotions and advertisement in their businesses.
Keywords: Business